Perancangan Mebel Bahan Kayu dan Kulit Sapi Samak Nabati - Mahendra, Yonata Buyung; Wicaksono, Agung; Jati, Ardian Mulyo; Kurniawan, Risky (Institut Seni Indonesia Yogyakarta, 2024)
The use of combined tanned cowhide leather in furniture is expected toprovide added value to the aesthetic and functional aspects. The combination ofmaterials and field division can provide compositional innovation on the visual side.The patterning technique is also part of the innovation that gives effect to the gameof composition from the division of the field on the furniture components. Inaddition, sewing can be done with ornamental techniques. Besides being part of theproduct construction, stitching techniques can be an accentuation to attractconsumer attention. Furniture product innovation can be done with the use of simpleleathergoods production equipment because it emphasizes the technical side ofmanual (hand made).The benefits of furniture design in this applied research are: 1) Productinnovation that will strengthen positioning to expand the target market as known inthe unique selling proposition (USP) strategy; 2) Increase the competitiveness offurniture products and at the same time product promotion by improving the qualityof its design; 3) Adding to the repertoire of science based on praxis methods in thefield of design and craft science. This applied research uses a combination ofqualitative research and design methods in which experimental steps are alsocontained. The objectives and benefits are expected to be achieved with thiscombination method. The problem is also expected to get a solution as a furnituremodel that emphasizes aesthetics and ergonomics for the international market.Theresults of this study are researchers formulated several points such as, marketacceptance and suitability of international trends, aesthetic and ergonomicinnovation, sustainability and function, sustainable aesthetic and ergonomicdevelopment, guidelines for designers and manufacturers.ABSTRAKBisnis mebel di Indonesia sangat marak beberapa tahun belakangan ini. Mebel merupakan objek yang seringkali digunakan sebagai elemen interior(Faisal & Utami, 2022). Pada awalnya mebel dibuat dari bahan kayu, namun dalam kondisi lima tahun terakhir memiliki pergeseran. Konsumen mulai menyukai perpaduan bahan dan bentuk dari produk mebel yang dibuat. Bahan yang digunakan sebagai kombinasi memiliki banyak jenis, diantaranya dengan rotan, kulit sintetis, plastik, dan bahan lainnya. Tidak terkecuali ada beberapa produk mebel yang menggunakan perpaduan kulit sapi, khususnya kulit samak nabati. Perpaduan kulit sapi samak nabati dengan kayu ini memiliki pasar tersendiri. Penggunaan bahan kulit sapi samak kombinasi pada mebel diharapkan dapat memberikan nilai tambah pada aspek estetika dan fungsi. Kombinasi bahan dan pembagian bidang dapat memberi inovasi komposisi pada sisi visualnya. Teknik pemolaan juga merupakan bagian dari inovasi yang memberikan efek pada permainan komposisi dari pemecahan bidang pada komponen mebel. Selain itu dalam penjahitan dapat dikerjakan dengan teknik hias. Selain menjadi bagian dari konstruksi produk, teknik jahitan dapat menjadi aksentuasi untuk menarik perhatian konsumen. Inovasi produk mebel dapat dikerjakan dengan penggunaan peralatan produksi barang kulit (leathergoods) sederhana karena mengedepankan sisi teknis manual (hand made). Material mebel direncanakan menggunakan kulit sapi samak nabati. Material dihasilkan oleh industri penyamak kulit yang tersebar di beberapa daerah. Di Indonesia terdapat beberapa sentra industri kulit, salah satunya di Kabupaten Magetan(Rara et al., 2020). Di sentra ini menghasilkan kulit tersamak yang banyak digunakan sebagai bahan baku produk kulit.